PENGEMBANGAN BUKU AJAR MENULIS CERPEN BERBASIS KARAKTERISTIK BUDAYA LOKAL DENGAN TEKNIK MENERUSKAN CERITA UNTUK SMK KABUPATEN GROBOGAN - Toharin Toharin; Sri Suciati; Harjito Harjito (Teks: Jurnal Penelitian Bahasa, Sastra, dan Pengajarannya, 2023)
AbstracTraditional learning activities of writing simple essays do not provide instructions to make it easier for students to write essays. As a result, students clash in writing down the material that comes to mind, causing frustration and considering learning boring. The purpose of this study is to develop a textbook on how to write short stories that meet the needs of students with storytelling skills based on local cultural characteristics. The research was conducted in the following phases using modified Borg and Gal research and development methods. 1) We collect information. 2) planning; 3) initial product development; 4) the first experiment. 5) Product Revision.